(untitled) (Tanzania Medical Journal, 2010)
Backbround: Due to its complex nature, anatomical pathology practice is inherently error prone. Currently, there is a tendency towards an increase in errors in pathology which stems out from medical practices of other medical disciplines at Muhimbili National Hospital and thus there is a need to have error reduction strategies combined with an attempt to apply these strategies. Objective: To determine errors in anatomic pathology in relation to the classic laboratory test cycle and discuss factors contributing to these errors. Study design: The study was a descriptive cross-sectional one in which the information analyzed was obtained from pre-analytic,analytic and pot-analytic phases of the anatomical pathology laboratory test cycle. Study setting: Muhimbili National Hospital in Dar es Salaam, Tanzania. Methodology: During the pre-analytic phase of the laboratory test cycle, request forms and specimen containers containing information of patients for histological analysis of the biopsy specimens were analyzed for important parameters which had a bearing in the diagnosis. Also parameters in the analytic phase of the laboratory test cycle were analyzed for errors. The parameters analyzed here were mainly those which occurred during the histologic specimen processing, in the taking-in room, at the microscope and by clerical personnel in the laboratory. Errors which were analyzed in postanalytic phase of testing related mainly to those which resulted from delivery of the reports or information to the clinician, untimely delivery of the reports and failure of the caregiver to see the reports at all. Results: In the pre-analytic phase of laboratory testing, errors were derived and analyzed from request forms for investigation fromclinicians and from information on the containers containing biopsy specimens. Out of 13 variables analyzed from the request forms, 11(84.6 %) had errors which differed in magnitude. The highest errorswere those which arose from misleading clinical information (90%),and missing of relevant clinical information of patients (90%). However, 8 variables were also analyzed from containers and the errors which ranked highest included mislabeling on the container (85%) followed by illegibly labeling of the container (75%) and others. On the part of the analytic phase of laboratory test cycle, there were 11 variables analyzed for analytic errors and 9 (81.8 %) variables had errors, among them typographic errors had the highest frequency (45%) followed by block mislabeling (35%). In the post-analytic phase of laboratory testing, there were 3 variableswhich were analyzed for errors. The variables analyzed and the errors which were found included; delivery of the report or information to wrong clinician (10%), untimely delivery of report to the clinician (35%) and failure of the caregiver to see the report at all was (15%). Conclusion and recommendations: The numerous errors amounted in the pre-analytic, analytic and post-analytic phases of laboratory test cycles in Anatomical pathology reinforces the need for effective quality control and quality assurance at all steps in laboratory test cycle. This will be possible only and only if factors that contribute to errors be reduced to an absolute minimum through error reduction strategies combined with an attempt to apply these strategies. Additionally, incremental adoption of information technology and automation along with improved training in patient safety and quality management can help reduce errors.Key words: Anatomical pathology, Pre-analytic, Analytic, Post-analytic, Errors, Laboratory test cycle